Deskripsi Keterampilan Generik Sains Siswa dalam Penyelesaian Soal Kimia pada Materi Hidrolisis Garam - Marnila Marnila; Erni Mohamad; Wiwin Rewini Kunusa; Astin Lukum; Julhim S. Tangio; Ahmad Kadir Kilo (Chemistry Education Department of Education and Teaching Faculty, 2023)
Generic science skills are very important for students, in addition to being able to improve students' understanding of concepts, by measuring generic science skills teachers can understand the character and skills possessed by students. This study aims to determine students' generic science skills in solving chemistry problems on salt hydrolysis material by high school students of class XI IPA SMA Muhammadiyah Batudaa. The focus of this study is to describe students' generic science skills in solving chemistry problems on salt hydrolysis material. The method used in this study is a qualitative descriptive research method using tests. The data was obtained through a description test, which was done in writing by 66 students at SMA Muhammadiyah Batudaa. The data that has been obtained will then be analyzed first through the code on the answers given by students, as well as through the scores of each component of the student answers. The results showed the achievement of generic science skills, namely indirect observation 78.41% (good), symbolic language 59.85% (less), law of cause and effect 62.06% (sufficient), logical frame 73.48% (sufficient), logical consistency 64.44% (sufficient). In general, the mastery of generic science skills of grade XI science students of Muhammadiyah Batudaa High School obtained an average percentage of 63.42%, including in the sufficient category.